2011
DOI: 10.1371/journal.pone.0023785
|View full text |Cite|
|
Sign up to set email alerts
|

Metagenomics of the Water Column in the Pristine Upper Course of the Amazon River

Abstract: River water is a small percentage of the total freshwater on Earth but represents an essential resource for mankind. Microbes in rivers perform essential ecosystem roles including the mineralization of significant quantities of organic matter originating from terrestrial habitats. The Amazon river in particular is famous for its size and importance in the mobilization of both water and carbon out of its enormous basin. Here we present the first metagenomic study on the microbiota of this river. It presents man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
180
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(201 citation statements)
references
References 66 publications
19
180
0
2
Order By: Relevance
“…The presence of amoABC genes in these data (Ghai et al, 2011) raises the question of whether chemoautotrophic ammonia oxidation might also be occurring in the lower Amazon reaches. Other freshwater habitats have been found to host Thaumarchaeota cells in the water column, including lakes and rivers (Urbach et al, 2001;Lehours et al, 2007;Auguet et al, 2011;Liu et al, 2011), where they can account for up to 47% of prokaryotic cells (Callieri et al, 2009).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The presence of amoABC genes in these data (Ghai et al, 2011) raises the question of whether chemoautotrophic ammonia oxidation might also be occurring in the lower Amazon reaches. Other freshwater habitats have been found to host Thaumarchaeota cells in the water column, including lakes and rivers (Urbach et al, 2001;Lehours et al, 2007;Auguet et al, 2011;Liu et al, 2011), where they can account for up to 47% of prokaryotic cells (Callieri et al, 2009).…”
Section: Introductionmentioning
confidence: 85%
“…Evidence of Archaea belonging to the phylum Thaumarchaeota has recently been found in metagenomic libraries of the upper reaches of Amazon River system (Ghai et al, 2011;Santos-Júnior et al, 2017). The presence of amoABC genes in these data (Ghai et al, 2011) raises the question of whether chemoautotrophic ammonia oxidation might also be occurring in the lower Amazon reaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghai et al analyzed metagenomic data from lakes, estuaries (Ghai et al, 2012), and rivers (Ghai et al, 2011), and found that acI members have a lower than expected GC genomic content. Martinez-Garcia et al (2012) used single-cell genomics and found that the origins of more than 80% of rhodopsins found among lake bacteria belong to the actinobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The term environment in this context refers not only to the classic outdoor terrestrial [1] and aquatic [2,3] domains, but also environments found within other organisms, like the gut [4,5] and associated matrices like probiotic supplements [6] or linked to other man-made scenarios like water purification [7] or during fermentation [8]. The field of metagenome analysis (metagenomics) has grown rapidly as the last 10 years have seen the development and establishment of next generation (also termed massively parallel) sequencing (NGS), a technique that has the potential to read over a billion sequences in a single run.…”
Section: Introductionmentioning
confidence: 99%